A novel based software testing process for user-friendly projects - Babu Rao, Kuntam (International Journal of Engineering and Technology, 2018)
Technology is growing very fast with various changes in Computer Systems. They are chasing human life. They are used in various fields around us. There are some governments who fund for computer systems. Still research related them is carry on and will carry. Mostly there services are used in defense purpose. Based on computer technology there are so many improvement in them, even embedded system are developed. Any system can present some risk to its ownerâ€™s, users and environment. Risk is based on low and high. Some systems present more risk than others. Those which are related to more risk are called safety-critical systems. Safety critical systems are categorized into dangerous systems whose failures could result in loss of life, loss of revenue, knowing them and unable to solve them is sabotage to property damage or damage to the environment. This paper focus better exercises for making good user-friendly software. Every system has two sides as if coin, one side is the physical system with hardware and other side is software. If anything is neglected, there is a chance of bug appears at run-time. This may cause loss to humans. Again a committee report will be preserved for future purpose. Â Â